LEGACY: Phase 2a Trial to Evaluate the Safety, Pharmacokinetics, and Pharmacodynamic Effects of the Anti-EL (Endothelial Lipase) Antibody MEDI5884 in Patients With Stable Coronary Artery Disease. Issue 12 (December 2021) - Ruff, Christian T.; Koren, Michael J.; Grimsby, Joseph; Rosenbaum, Anton I.; Tu, Xiao; Karathanasis, Sotirios K.; Falloon, Judith; Hsia, Judith; Guan, Ye; Conway, James; Tsai, Lan-Feng; Hummer, B. Timothy; et al.
Abstract : Objective: Functional HDL (high-density lipoprotein) particles that facilitate cholesterol efflux may be cardioprotective. EL (endothelial lipase) hydrolyzes phospholipids promoting catabolism of HDL and subsequent renal excretion. MEDI5884 is a selective, humanized, monoclonal, EL-neutralizing antibody. We sought to determine the safety, pharmacokinetics, and pharmacodynamic effects of multiple doses of MEDI5884 in patients with stable coronary artery disease. Approach and Results: LEGACY was a phase 2a, double-blind, placebo-controlled, parallel-design trial that randomized 132 patients with stable coronary artery disease receiving high-intensity statin therapy to 3 monthly doses of 1 of 5 dose levels of MEDI5884 (50, 100, 200, 350, or 500 mg SC) or matching placebo. The primary end point was the safety and tolerability of MEDI5884 through the end of the study (day 151). Additional end points included change in HDL cholesterol and cholesterol efflux from baseline to day 91, hepatic uptake of cholesterol at day 91, changes in various other lipid parameters. The incidence of adverse events was similar between the placebo and MEDI5884 groups. In a dose-dependent manner, MEDI5884 increased HDL cholesterol up to 51.4% ( P <0.0001) and global cholesterol efflux up to 26.2% ([95% CI, 14.3–38.0] P <0.0001). MEDI5884 increased HDL particle number up to 14.4%. At the highest dose tested, an increase in LDL (low-density lipoprotein) cholesterol up to 28.7% ( P <0.0001) and apoB (apolipoprotein B) up to 13.1% ( P =0.04) was observed with MEDI5884. However, at the potential target doses for future studies, there was no meaningful increase in LDL cholesterol or apoB. Conclusions: Inhibition of EL by MEDI5884 increases the quantity and quality of functional HDL in patients with stable coronary artery disease on high-intensity statin therapy without an adverse safety signal at the likely dose to be used. These data support further clinical investigation. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03351738. Abstract : Supplemental Digital Content is available in the text.